Issues and challenges of management education in Malaysia - Muniapan, Balakrishnan (2007)
This paper explores some of the pertinent issues and challenges of management education in Malaysia. Management education has seen a remarkable growth in the recent years as reflected in the steep rise in the number of institutes offering programs in management at various levels. These institutions of higher learning (IHL) which offers management education; need to play a major role in producing the right quality and quantity of managers to meet the requirements of marketplace. This is a qualitative paper based on inputs from informal discussions with several management educators, management consultants, management students and managers, which had taken place at several meetings, seminars and conferences over the last five years and also a review of literature in field of management education. This paper also provides some recommendations to improve the effectiveness of management education in the context of Malaysia.